LIGHT VARIATION OF AN R CRB STAR IN SCULPTOR - PISMIS, P (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
The variations of the luminosity bf the star SPC 4 estimated from photographic plates are here presented. The observational material covers an interval of about 60 years. From 1962 to 1968 the ample photographic material is taken with the Schmidt camera a
BOL OBS TONAN TACUB
Keywords: LIGHT, VARIATION, STAR, SCULPTOR; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS